Model Of Emergency Department Nurse Performance Improvement Based on Association of Individual Characteristic, Organization Characteristic and Job Characteristic - Maria Margaretha Bogar; Nursalam Nursalam; Yulis Setiya Dewi (Universitas Airlangga, 2013)
Introduction: Nursing care is integral part of health care and having important role in management of patient with emergency condition. The purpose of this research was to develop nurse performance improvement model based on individual, organization and job characteristics association in Emergency Department of RSUD dr TC Hillers Maumere. Method: This was an explanative survey by cross sectional approach held on July -August 2012. Respondents in this study were 22 nurses and 44 patients were obtained by purposive sampling technique. Data were analyzed by partial least square test and signi fi cant t value > 1.64 (alpha 10%). Result: Results showed that individual characteristic had effect on nurse performance (t = 7.59), organization characteristic had effect on nurse performance (t = 2.03) and job characteristic didn’t have effect on nurse performance (t = 0.88). Nurse performance had effect on patient satisfaction (t = 6.54) but nurse satisfaction didn’t have effect on nurse performance (t = 1.31), and nurse satisfaction didn’t have effect either on patient satisfaction (t = 0.94). Discussion: This research concluded that individual characteristics which in fl uence nurse performance in nursing care were ability and skill, experience, age, sex, attitude and motivation. Organization characteristic that influence nurse performance was reward while job characteristic that include job design and feedback didn’t influence nurse performance in nursing care. Nurse performance influenced patient satisfaction but nurse satisfaction didn’t influence patient satisfaction and nurse performance.